Evaluation of Models of Parkinson's Disease - Jagmag, Shail A.; Tripathi, Naveen; Shukla, Sunil D.; Maiti, Sankar; Khurana, Sukant (Frontiers in Neuroscience, 2016)
Parkinson’s disease is one of the most common neurodegenerative diseases. Animal models have contributed a large part to our understanding and therapeutics developed for treatment of PD. There are several more exhaustive reviews of literature that provide the initiated insights into the specific models; however a novel synthesis of the basic advantages and disadvantages of different models is much needed. Here we compare both neurotoxin based and genetic models while suggesting some novel avenues in PD modelling. We also highlight the problems faced and promises of all the mammalian models with the hope of providing a framework for comparison of various systems.